French your way 2.0 beginner - intermediate - Syracuse Language Systems (New York : Syracuse, 1997)
Complete interactive course; Conversations - Grammar - Games - Activities
System requirements: IBM PC or compatible PC; 486DX33 or faster microprocessor; Windows 3.1 or 95 operating system; 8MB of RAM; 16MB of hard drive space; SVGA 256-colors display; CD-ROM drive; 16 bit sound card; Speaker or headphones; Mouse; Microphone (for Speech Regognition and record/playback)
Keywords: French language -- Study and teaching -- CD-ROMs.; French language -- Self-instruction.; French language -- Computer-Assisted instruction; CD-ROMs.